Regulatory T cells administration reduces anxiety-like behavior in mice submitted to chronic restraint stress - Cepeda, Yamila; Elizondo-Vega, Roberto; Garrido, Camila; Tobar, Catalina; Araneda, Matías; Oliveros, Patricia; Ordenes, Patricio; Carril, Claudio; Vidal, Pía M.; Luz-Crawford, Patricia; García-Robles, María. A.; Oyarce, Karina (Frontiers in Cellular Neuroscience, 2024)
Background Major depression disorder (MDD) and anxiety are common mental disorders that significantly affect the quality of life of those who suffer from them, altering the person’s normal functioning. From the biological perspective, the most classical hypothesis explaining their occurrence relies on neurotransmission and hippocampal excitability alterations. However, around 30% of MDD patients do not respond to medication targeting these processes. Over the last decade, the involvement of inflammatory responses in depression and anxiety pathogenesis has been strongly acknowledged, opening the possibility of tackling these disorders from an immunological point of view. In this context, regulatory T cells (Treg cells), which naturally maintain immune homeostasis by suppressing inflammation could be promising candidates for their therapeutic use in mental disorders. Methods To test this hypothesis, C57BL/6 adult male mice were submitted to classical stress protocols to induce depressive and anxiety-like behavior; chronic restriction stress (CRS), and chronic unpredictable stress (CUS). Some of the stressed mice received a single adoptive transfer of Treg cells during stress protocols. Mouse behavior was analyzed through the open field (OFT) and forced swim test (FST). Blood and spleen samples were collected for T cell analysis using cell cytometry, while brains were collected to study changes in microglia by immunohistochemistry. Results Mice submitted to CRS and CUS develop anxiety and depressive-like behavior, and only CRS mice exhibit lower frequencies of circulating Treg cells. Adoptive transfer of Treg cells decreased anxiety-like behavior in the OFT only in CRS model, but not depressive behavior in FST in neither of the two models. In CRS mice, Treg cells administration lowered the number of microglia in the hippocampus, which increased due this stress paradigm, and restored its arborization. However, in CUS mice, Treg cells administration increased microglia number with no significant effect on their arborization. Conclusion Our results for effector CD4+ T cells in the spleen and microglia number and morphology in the hippocampus add new evidence in favor of the participation of inflammatory responses in the development of depressive and anxiety-like behavior and suggest that the modulation of key immune cells such as Treg cells, could have beneficial effects on these disorders.